Do self-translating poets have equally distributed equivalent words in the target and original texts? A corpus examination of Yu Guangzhong's poems - Li, Shengnan; Halim, Hazlina Abdul; Mamat, Roslina (Sciedu Press, 2024)
This article examines the utilization of high-frequency words in Yu Guangzhong's self-translated poetry through a corpus-driven analysis. The objective is to explore the presence of equivalence and inequivalence in the translations executed by Yu Guangzhong himself. The utilization of modal verbs, lexical bundles, and keywords has been analyzed in various contexts, such as novels and speeches.However, studies that compare disparities in the use of high-frequency words between the source and target languages within poetry translation are scarce. The original and self-translated poetry corpora of Yu Guangzhong have been constructed at the word level to enhance the original texts' co-occurrence and corresponding translations. In the comprehensive self-translation of his eighty-five poems, Yu Guangzhong encounters challenges in achieving an equitable distribution of equivalent words between the target and original texts. It isobserved that most high-frequency words in Yu Guangzhong's original and target texts lack equivalence in use and meaning. Although two of the three poems analyzed individually mainly achieve equivalence, this discrepancy might be attributed to the translator's utilization of literal and word-for-word translations. © 2024 The Author(s).